(untitled) (Global Journal of Management and Business Research, 2021)
Climate change, lack of resources and little market accessibility are current threats to food production, food accessibility, and food security. Climate-smart Agriculture is the way to turn around the situation to more resilience and higher Agricultural productivity leading to improved food accessibility and security status. This paper utilized a cross-sectional survey research design and primary data to examine the effect of smart Agri-preneurship dimensions on food accessibility in South-West, Nigeria. The study adopted Cochran, Hatzes, Butler and Marcy formula (1997) to ascertain the sample size. A reliable and valid questionnaire was administered to 558 Agri-preneurs. The regressed constructs revealed a positive and significant effect of smart Agri-preneurship on food affordability (Adj. R2=0.642, F (6551) =167.442 and p=0.000). The study concluded that smart Agri-preneurship dimensions affected food accessibility in South-West, Nigeria.